The induction and function of the anti-inflammatory fate of TH17 cells - Hao Xu (Nature Portfolio, 2020)
CD4+ T helper cells producing IL-17A (TH17 cells) can take on pathogenic or anti-inflammatory functions in context-specific manners. Here the authors show that the anti-inflammatory fate of TH17 cells contributes, via TGF-β signaling and induction of IL-10, to host immune tolerance, but also simultaneously dampens protective immunity against S. aureus.